Error correcting code based on finite automaton and representation of numbers in the two-base numeration system - Zavadskyi, I.O. (PROBLEMS IN PROGRAMMING, 2025)
A new error correcting code is introduced. It combines several approaches to constructing of error correcting codes: utilizing the arithmetic properties of numbers, represented by input bit sequences, encoding by finite automaton and by simple block code. Either encoding and decoding algorithms are presented.Prombles in programming 2014; 2-3: 205-211